The influence of heating sequence on deformation of steel plate in induction heating process - ZHANG Xuebiao; WANG Junqi; WANG Qiao (Xibei Gongye Daxue Xuebao)
The line heating formation of a complex curved plate needs multiple heating lines. Heating sequence is an important factor of influence on the formation to obtain the curved surface plate of a particular shape. The paper uses the elastic-plastic inherent strain finite element model to study the overall deformation of a steel plate in different heating sequences. Meanwhile, it carries out experiments on the induction heating of two roll bending plates with multiple heating lines, using the heating sequence as the only variable. The difference in height between the calculation value and measurement value of the two plates meets the engineering application requirements. The elastic-plastic inherent strain finite element model can be used to calculate the deformation of the steel plate in different heating sequences. The three-dimensional surface location and hypothesis test analysis of data on difference between two steel plates show that the heating sequence of multiple heating lines has a significant effect on steel plate deformation.